The Effect of STAD Type Cooperative Learning Models and Students' Social Skills on the Fifth Grade Students Learning Outcomes at Cinta Rakyat State Primary School - Sri Astuti; Rachmat Mulyana; Siman Siman (BIRCU, 2021)
This study aims to investigate: (1) the difference in the effect of STAD type cooperative learning model and jigsaw type on the fifth grade student learning outcomes at Cinta Rakyat state primary school, (2) the difference in learning outcomes between students with high social skills and low social skills at grade five and (3) the interaction between cooperative learning approaches and social skills on the learning outcomes of fifth grade students of state primary school. This research is a quasi experimental research. The population of this study is students in class V1, V2, V3 at Cinta Rakyat state primary school. The sample in this study is class Va for the experimental class that is taught by using STAD type cooperative learning and the control class is Vb which is taught by using jigsaw type cooperative learning. The results show that: (1) the learning outcomes of students who are taught by STAD cooperative learning, 25.70. It is greater than students who are taught by jigsaw cooperative learning, it is 21.83, (2) the learning outcomes of students taught using high social skills obtains an average score of 25.07, while the learning outcomes of students who use low social skills obtains an average score of 22.63, and (3) there is no significant interaction between the use of learning and students' social skills (high, and low) in influencing learning outcomes.